Optimalisasi Fungsi Manajemen Keperawatan dalam Discharge Planning pada Pasien Gagal Jantung - Esti Giatrininggar; La Ode Abdul Rahman; Dewi Meilina (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the implementation of the head of the room management function in discharge planning in heart failure patients. The research method uses a case study approach with interviews, document review, observation, and analysis using Fishbone. The study results showed that the hospital still needed a standardized form for implementing heart failure discharge planning. The modified form can help the head of the room as a guide in implementing discharge planning. Socialization is carried out through audio-visual media to nurses. The results of the evaluation show that the audio-visual media assists nurses in increasing knowledge about the implementation of discharge planning and the updated heart failure discharge planning form. In conclusion, form modification and socialization using audio-visual media can assist the head of the room in carrying out management functions and increasing nurses' knowledge. Keywords: Management Function, Discharge Planning, Head of Room